Qualidade da água do sistema de abastecimento público da cidade de Maceió-AL - Barbosa, Rita de Cássia Vieira de Almeida (2013)
Water is one of the main substances ingested by humans, so that it is an essential element for life. According to the World Health Organization, 80% of the recorded diseases occurring in the underdeveloped world are caused by ingestion of water containing pathogenic microorganisms. This research has aimed at identifying the physic-chemical characteristics (pH, Cl, color e turbidity) and the bacterial population (coliforms, E. coli and heterotrophic bacteria) of the water supplied by the public network of the city of Maceio, at points of entry and points of exit- water tank. To that aim, 54 establishments (18 public schools, 18 basic health unities and 18 restaurants) were selected, in each of which two samples were collected, one at the entry point and one at the exit point - water tank, summing up 108 samples. The samples were taken; at both, dry and rainy season, 11 samples at the exit point of the reservoirs, 03 samples at the entry point and the exit point and 3 at the water treatment plants, in order to identify differences between dry and rainy seasons. The samples were evaluated according to the following parameters: total coliforms, Escherichia coli, heterotrophic bacterial count, pH determination, turbidity, color and free residual chlorine. It was observed a decrease in the microbiological physicchemical quality of water in the entry network and the building reservoir at the 54 i establishments, in both periods, dry and rainy season. It was observed reduction of quality of stored water in restaurants during rainy season, water impairment in the health units in the rainy season. There was no change in the water in the building reservoirs and an observed increase of water contamination in the distribution network in the schools in the rainy season and a reduction of the residual clorine level in the building reservoirs in the rainy season. Therefore, it is recommended preventive maintenance, cleaning and disinfection of these building reservoirs in order to maintain the same quality of the water distribution network.